DevOps as a culture of interaction and deployment in an insurance company. - et. al., Angel Salvatierra Melgar , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study provides the contributions of the implementation and development of DevOps in the integration and deployment of software in the organization due to problems previously detected regarding the speed and quality of reports. The arguments assumed from a DevOps culture, respond to: techniques and practices of continuous integration, continuous deployment, test automation, collaboration, automation, measurement and monitoring; these facts, was thanks to the implementation of the pre-experimental research design of applied type, in a sample of 48 weekly sprints, with a total of 96 user stories of the project taken from the organization. The study allowed to demonstrate the decrease of the Cycletime of days on average, increase the frequency of code release and increase the percentage of attention ratio, based on these results, it was possible to demonstrate the improvement of the speed during the deployment and quality of software processes, these results were thanks to the adoption of DevOps as a culture of interaction and deployment in an organization in the insurance sector.